STRATEGI INOVATIF DALAM EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS KURIKULUM MERDEKA UNTUK MENUMBUHKAN SIKAP FASTABIQUL KHOIROT DI SMP NEGERI 38 MEDAN - Dinda Amalia; Arlina Sirait (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The evaluation of Islamic Religious Education learning within the Merdeka Curriculum remains predominantly oriented toward cognitive achievement, resulting in the insufficient internalization of fastabiqul khairat values in students’ behavior. This study aims to examine innovative evaluation strategies in Islamic Religious Education learning based on the Merdeka Curriculum to foster fastabiqul khairat attitudes among students at SMP Negeri 38 Medan. The study employs a qualitative approach with a phenomenological research design to understand teachers’ experiences and practices in designing and implementing learning evaluation. Research data were collected through observation, in-depth interviews, and documentation, with data sources comprising Islamic Religious Education teachers, school leaders, and students of SMP Negeri 38 Medan. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data credibility was ensured through source triangulation and technique triangulation. The findings indicate that innovative evaluation strategies based on authentic assessment are able to encourage the internalization of fastabiqul khairat values through the continuous development of students’ spiritual, social, and moral attitudes, in line with the objectives of Islamic Religious Education and the principles of the Merdeka Curriculum.